Der funktional-pragmatische Ansatz zur Grammatikvermittlung. Plädoyer für seinen Einsatz im (schulischen) DaF-Unterricht - Malloggi, Patrizio (Kritik. Rivista di letteratura e critica culturale, 2023)
The communicative approach developed in the 1980s logically led to the goal of thinking of grammar teaching in terms of communicative situations. According to this goal, this article deals with grammar teaching that can be defined as functional-pragmatic, since grammatical phenomena are regarded as means of realising communicative actions and are examined in connection with their semantic and pragmatic properties. This article aims at presenting a non-traditional approach to the teaching of spatial prepositions that contributes to the development of communicative (oral and written) competence of learners of German as foreign language.